Differences in Self Image of Male Students and Female Students Using TikTok Social Media - Indrama, Leony Sarah; Yendi, Frischa Meivilona; Ardi, Zadrian; Handayani, Puji Gusri; Suri, Gusni Dian (Universitas Negeri Padang, 2024)
Communication between teenagers in the social environment and school environment has now mastered technology that uses internet networks, namely social media. One type of social media is TikTok. Social media which is used as a tool to shape a person's image becomes an encouragement for a broader view of something. Self-image is the way a person sees himself, a person's reflection or picture of himself. This research is motivated by individuals who have different self-images, some have positive and negative self-images, as well as the self-images of men and women. This research aims to test whether there are differences in the self-image of male students and female students who use TikTok. The research method used is a quantitative method with a comparative descriptive approach because it looks at the differences between male and female students. The sample for this research was 254 students at SMP Negeri 7 Padang who were selected using proportional stratified random sampling techniques. The results of the research show that there is no significant difference between the self-image of male and female students at SMP Negeri 7 Padang.